Technical note - homogeneity of Gafchromic EBT2 film - Breithaupt, Bernadette; Martišíková, Mária; Jäkel, Oliver (Medical physics, 2010)
Purpose: The self-developing Gafchromic® EBT film is a radiochromic film, widely used for relative photon dosimetry. Recently, the manufacturer has replaced the well-investigated EBT film by the new Gafchromic® EBT2 film. It has the same sensitive component and, in addition, it contains a yellow marker dye in order to protect the film against ambient light exposure and to serve as a base for corrections of small differences in film response. Furthermore, the configuration of the film layers as well as the binder material have been changed in comparison to the EBT film. When investigating the properties of EBT2 film, all characteristics were found to be similar to those of EBT film, except for the film response homogeneity. Thus, in this article special focus was put on examining the homogeneity of EBT2 film. Methods: A scan protocol established for EBT film and published previously was used. The uniformity of the film coloration was investigated for unirradiated and irradiated EBT2 film sheets. The dose response of EBT2 film was measured and the influence of film inhomogeneities on dose determination was evaluated. Results: Inhomogeneities in pixel values of up to ±3.7% within one film were detected. The relative inhomogeneities were found to be approximately independent of the dose. Nonuniformities of the film response lead to uncertainties in dose determination of ±8.7% at 1 Gy. When using net optical densities for dose calibration, uncertainties in dose determination amount to more than ±6%. Conclusions: EBT2 films from the lot investigated in this study show response inhomogeneities, which lead to uncertainties in dose determination exceeding the commonly accepted tolerance levels. It is important to test further EBT2 lots regarding homogeneity before using the film in clinical routine.
First published: 25 March 2010
Gesehen am 24.03.2023